2013
DOI: 10.1371/journal.pone.0060790
|View full text |Cite
|
Sign up to set email alerts
|

Annexin Peptide Ac2-26 Suppresses TNFα-Induced Inflammatory Responses via Inhibition of Rac1-Dependent NADPH Oxidase in Human Endothelial Cells

Abstract: The anti-inflammatory peptide annexin-1 binds to formyl peptide receptors (FPR) but little is known about its mechanism of action in the vasculature. Here we investigate the effect of annexin peptide Ac2-26 on NADPH oxidase activity induced by tumour necrosis factor alpha (TNFα) in human endothelial cells. Superoxide release and intracellular reactive oxygen species (ROS) production from NADPH oxidase was measured with lucigenin-enhanced chemiluminescence and 2′,7′-dichlorodihydrofluorescein diacetate, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 56 publications
6
20
0
Order By: Relevance
“…[15,35,36] In addition, it was reported that ANXA1 peptide Ac2-26 suppressed TNF-α-induced inflammatory response via inhibition of VCAM-1 and ICAM-1 in endothelial cells. [37] In the present study, HDL-induced ANXA1 inhibited cell surface VCAM-1, ICAM-1 and E-selectin, and secretion of MCP-1, IL-8, VCAM-1 and E-selectin in TNF-α-activated endothelial cells. Our novel results indicated that ANXA1 was a crucial mediator for anti-inflammation, which enriched protective mechanism of HDL.…”
Section: Hdl-induced Anxa1 Partially Inhibited Cellsupporting
confidence: 55%
“…[15,35,36] In addition, it was reported that ANXA1 peptide Ac2-26 suppressed TNF-α-induced inflammatory response via inhibition of VCAM-1 and ICAM-1 in endothelial cells. [37] In the present study, HDL-induced ANXA1 inhibited cell surface VCAM-1, ICAM-1 and E-selectin, and secretion of MCP-1, IL-8, VCAM-1 and E-selectin in TNF-α-activated endothelial cells. Our novel results indicated that ANXA1 was a crucial mediator for anti-inflammation, which enriched protective mechanism of HDL.…”
Section: Hdl-induced Anxa1 Partially Inhibited Cellsupporting
confidence: 55%
“…HMECs and MDA-MB-231 were seeded in 12-well plates (BD Falcon TM , New South Wales, Australia) and transfected using Lipofectamine 2000 (Life Technologies, Victoria, Australia) 400 ng of pGL3-NF-jB and 100 ng of a reference plasmid (pRL-SV40; Promega, Wisconsin, USA) simultaneously. Luciferase assay was performed using dual luciferase kit from Promega (Promega, Wisconsin, USA) as described previously [22].…”
Section: Nf-jb-binding Luciferase Reporter Assaymentioning
confidence: 99%
“…Additional evidence in dermal microvascular ECs indicated that activation of NF-kB, a downstream effector of TNF-aemediated inflammatory signaling, was involved in TNF-aeinduced ROS generation and involved NADPH oxidase activation. 15 In aortic vascular ECs, cross talk between oxidative and inflammatory pathways was proposed to affect endothelial dysfunction and cardiovascular disease. 16 We previously found that VEGF promoted CEC migration by activating the small GTPase Rac1.…”
mentioning
confidence: 99%